Radion Production in e\(^+\)e\(^-\) Collisions - Giang, Bui Thi Ha; Thuy, Dao Thi Le; Dai, Nguyen Van; Soa, Dang Van (Communications in Physics, 2015)
We analyse the potential of the e+e− collisions to search for the radion in theRandall-Sundrum model, where compactification radius of the extra dimension isstabilized by the radion, which is a scalar field lighter than the graviton Kaluza- Klein states. The radion production in the high energy e+e− colliders withpolarization of e+, e− beams was studied in detail. Numerical evaluation showsthat if the radion mass is not too heavy with the mass order of GeV then thereaction can give observable cross section in high energy colliders with the highdegree of polarization.